The nociceptive withdrawal reflex does not adapt to joint position change and short-term motor practice - Eckert, Nathan (F1000Research, 2013)
The nociceptive withdrawal reflex is a protective mechanism to mediate interactions within a potentially dangerous environment. The reflex is formed by action-based sensory encoding during the early post-natal developmental period, and it is unknown if the protective motor function of the nociceptive withdrawal reflex in the human upper-limb is adaptable based on the configuration of the arm or if it can be modified by short-term practice of a similar or opposing motor action. In the present study, nociceptive withdrawal reflexes were evoked by a brief train of electrical stimuli applied to digit II, 1) in five different static arm positions and, 2) before and after motor practice that was opposite (EXT) or similar (FLEX) to the stereotyped withdrawal response, in 10 individuals. Withdrawal responses were quantified by the electromyography (EMG) reflex response in several upper limb muscles, and by the forces and moments recorded at the wrist. EMG onset latencies and response amplitudes were not significantly different across the arm positions or between the EXT and FLEX practice conditions, and the general direction of the withdrawal response was similar across arm positions. In addition, the force vectors were not different after practice in either the practice condition or between EXT and FLEX conditions. We conclude the withdrawal response is insensitive to changes in elbow or shoulder joint angles as well as remaining resistant to short-term adaptations from the practice of motor actions, resulting in a generalized limb withdrawal in each case. It is further hypothesized that the multisensory feedback is weighted differently in each arm position, but integrated to achieve a similar withdrawal response to safeguard against erroneous motor responses that could cause further harm. The results remain consistent with the concept that nociceptive withdrawal reflexes are shaped through long-term and not short-term action based sensory encoding.